Analisa Pengaruh Akuntansi Forensik, Whistleblowing, dan Audit Investigatif Terhadap Pencegahan Fraud - Yuli Meliana; Joanne Intania Rut Simunapendi; Tries Ellia Sandari (Pusat Riset dan Inovasi Nasional, 2024)
A crime that often occurs in both government and private environments is fraud. Fraud prevention can be done through the influence of forensic accounting, whistleblowing and investigative audits. The method used is literature study, and the results of data analysis are processed descriptively. The results are that forensic accounting and whistleblowing have an influence on fraud prevention, and investigative audits in several studies have been stated to have an influence, but those that state investigative audits also have no significant effect on fraud prevention.